Global changes ethics, politics and environment in the contemporary technological world - Luca Valera; editors; Juan Carlos Castilla (Switzerland Springer Nature, 2020)
This book offers an authoritative analysis of the challenges that have arisen as a result of modern technologies. It covers several environmental problems, such as climate change, overexploitation of natural resources, loss of natural habitats, pollution and human population growth, and discusses practical scenarios for sustainable human dwelling of our planet. Adopting an interdisciplinary approach, the first part introduces (3z(Bglobal changes(3y(B, describing how they are happening in reality, and the challenges arising from them. The second part introduces methodological approaches borrowed from various disciplines, such as engineering, management science, philosophy and theology, which can help deal with the contemporary challenges resulting from global changes. Lastly, the third part discusses some of the themes presented in the light of novel concepts, such as the Anthropocene, and includes interesting proposals and ideas about how human beings could dwell the Earth in this new age. Offering a comprehensive theoretical reflection on the relation between technology, environment and human beings, it also provides a practice-oriented guide for researchers and decision-makers working on a new ethical paradigm of acting in the Anthropocene.s
Keywords: Technological innovations--Moral and ethical aspects; Environmental ethics